2013
DOI: 10.1007/s00423-013-1093-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after surgery for primary hyperaldosteronism may depend on KCNJ5 tumor mutation status: a population-based study from Western Norway

Abstract: KCNJ5 mutations are associated with a better surgical outcome. Preoperative identification of the mutation status might have impact on surgical strategy (total vs. subtotal adrenalectomy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
5
20
0
1
Order By: Relevance
“…All mutation‐positive patients had confirmed APAs on histopathology, with two patients having associated background hyperplasia. These findings are in concordance with other large series, which demonstrate that mutations in KCNJ5 are confined to patients with APA . Overall tumour prevalence of 41% is in line with other larger series .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All mutation‐positive patients had confirmed APAs on histopathology, with two patients having associated background hyperplasia. These findings are in concordance with other large series, which demonstrate that mutations in KCNJ5 are confined to patients with APA . Overall tumour prevalence of 41% is in line with other larger series .…”
Section: Discussionsupporting
confidence: 93%
“…A recent landmark article by Choi and colleagues identified somatic mutations (G151R and L168R) in the KCNJ5 gene that affected the Kir3.4 potassium channel found in the ZG . Subsequent studies have also confirmed the presence of these somatic mutation in up to 45% of patients with APAs . Interestingly, germ line mutations (G151E) in KCNJ5 have also been noted in patients with familial hyperaldosteronism type III …”
Section: Introductionmentioning
confidence: 97%
“…The total prevalence of KCNJ5 somatic mutations in APAs was 65.2% in a Japanese report [10], 76.8% in a Chinese report [11] and 59.5% in a Taiwanese report [12]. Evidence showed KCNJ5 -mutant carriers were younger, had higher levels of preoperative aldosterone, more severe hypokalemia, and had a better hypertension prognosis after adrenalectomy than non-mutant carriers [9, 1214]. Although it is well known that primary aldosteronism increases cardiovascular risk [15, 16], we are interested in knowing whether KCNJ5 -mutant carriers have a higher risk of cardiovascular damage than non-mutant carriers.…”
Section: Introductionmentioning
confidence: 99%
“…15 Currently, there has not been agreement on the correlation between KCNJ5 mutations and response to adrenalectomy. 15,16 Therefore, a greater number of cases need to be studied to evaluate the clinical characteristics of patients with and without somatic mutations in APAs. There has been no study investigating somatic mutations in APAs in China thus far.…”
mentioning
confidence: 99%